Chosen Instrument of God: Acts 9:15 In Light of Paul’s Pastoral Ministry - Sewakpo, Honore (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2023)
Paul’s call, which explicates that he is a chosen instrument of God, and the success of his pastoral ministry dovetail with his Damascus road experience. Paul, who was a persecutor of Christians experienced a conversion on the road to Damascus and became an apostle to the Gentiles. Existing studies on this remarkable experience have focused more on controversies surrounding the unusual nature of the event and its veracity than on its contribution to the success of Paul’s ministry. This study, therefore, investigates Acts 9:15 with a view to establishing the nexus of Paul’s Damascus road experience to his call and pastoral ministry. Using Ralph Martin’s grammatico-historical approach to biblical exegesis, the paper reveals that the divine grace that characterised Paul’s call to the ministry, the nature and results of his preaching, and the recognition and support that he had received from the church and its leadership enabled Paul to have an effective pastoral ministry. It recommends that the promotion of the gospel and zeal for Christian message must correspond to the proclamation of the crucified Christ.